2006
DOI: 10.1007/s10563-006-9015-8
|View full text |Cite
|
Sign up to set email alerts
|

Porous microfibers and microhoneycombs synthesized by ice templating

Abstract: R e c e n t l y we i n t r o d u c e d t h e " i c e t e mp l a t i n g " me t h o d , a new method which allows the synthesis of nanoporous materials with unique morphology, such as microfibers and microhoneycombs. In this method, materials are synthesized by freezing their parent hydrosols or hydrogels unidirectionally. Ice crystals which grow within the precursor during freezing act as the template. Therefore, the template can be easily removed through simple thawing and drying, which is a unique and benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Li et al [325] prepared honeycomb graphitic-carbon films containing an array of 75 nm diameter pores, and found that these honeycomb carbon films dramatically improve rate capabilities relative to thin carbon films used as Li + -insertion anodes. In addition, a porous material with hierarchical pore sizes at micro-, meso-and macrometer scales has been proposed to be ideal for overall performance enhancement [48]. For this, "ice templating" method was employed to synthesize nanoporous materials with micro-honeycombs (Fig.…”
Section: Energy Conversionmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al [325] prepared honeycomb graphitic-carbon films containing an array of 75 nm diameter pores, and found that these honeycomb carbon films dramatically improve rate capabilities relative to thin carbon films used as Li + -insertion anodes. In addition, a porous material with hierarchical pore sizes at micro-, meso-and macrometer scales has been proposed to be ideal for overall performance enhancement [48]. For this, "ice templating" method was employed to synthesize nanoporous materials with micro-honeycombs (Fig.…”
Section: Energy Conversionmentioning
confidence: 99%
“…In Fig. 2, we summarized representative applications of the most typical artificial honeycomb structures, which can be divided into three categories depending on scale, i.e., the traditional engineering field, the micro and nanofabrication field, and the biomedicine field [36,[44][45][46][47][48][49][50][51][52][53][54]. It can be seen that new applications of honeycomb structures have been constantly launched in the traditional engineering field (e.g., Hex tower designed by Michel Rojkind and airless honeycomb tire), in innovative micro-and nano-scale fabrications (e.g., lithiated silicon honeycombs [46]), as well as in biomedical applications (e.g., scaffold designed with accordion-like honeycomb [44]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The template can be easily removed through simple thawing and drying; this is a unique and beneficial feature of this method, overcoming the problems inherent in other templating techniques requiring the use of expensive templates removed through either high temperature or extremely high or low pH conditions [14]. The process is environmentally friendly, since it uses water as a removable template, highly versatile, and the resulting structures are highly tunable by changing process conditions.…”
Section: Introductionmentioning
confidence: 99%
“…An ice template may be produced in two ways: freeze-gelation and unidirectional freezing. It has been found that the morphology can change from microhoneycombs to polygonal fibers, passing through intermediate morphologies (lamella sheets, flat fibers), as is commonly found in silica and resorcinolformaldehyde sol-gel systems [12,49,76]. At the start the hydrogels presented a micro-honeycomb structure and when hydrogels were frozen unidirectionally microfibers with polygonal cross sections were obtained [76] (Fig.…”
Section: Scaffold Techniquesmentioning
confidence: 74%